What would the Marshal do?: Historical heroes as role models in contemporary martial arts (Revista de Artes Marciales Asiáticas, 2024)
Many martial arts systems have their own revered heroes, such as mythical founders and leaders of notable schools. The paper draws on ethnographic research conducted on The Blade Academy, an expanding historical European martial arts (HEMA) school in the United Kingdom. Among pedagogic strategies used by the lead instructors and their core followers are narratives about historic figures whose heroic beliefs and deeds should be respected and even emulated by practitioners. This article explores the case study of 12-13th century Norman-English knight William Marshal, who is used as a principal model for leadership, martial valour, economic success and moral activity by the lead instructor. We examine idealised models of chivalry that such modern martial artists aspire to follow despite them living within very different societies and value systems. We conclude by considering the merits of revisiting historical figures who might act as role models for modern teachers and their students.